The foundations of gentry life the Multons of Frampton and their world 1270-1370 - Coss, Peter R. (New past & present book series., 2010)
Peter Coss examines the formative years of the English gentry. In doing so, he explains their lasting characteristics during a long history as a social elite, including adaptability to change and openness. The book explores the material culture of the gentry, their concern with fashion and obsession with display.